Ajaran Ekstrem Gereja Masehi Advent Hari Ketujuh dan Ancaman bagi Eksistensi GMIM - Suoth, Novita (Educatio Christi, 2020)
The rise of various denominations around the world has an impact on the land of Minahasa, where most of the congregations are part of the ministry of the Evangelical Christian Church in Minahasa. There are various strategies employed by various denominations to influence the thinking of church members. GMIM congregation members have not escaped other denominational strategies of "stealing the sheep" but by employing unbiblical ways of influencing church members. This was done by the Seventh-day Adventist Church (GMAHK). The influence of the GMAHK teachings that took unethical approaches resulted in some church members in the scope of the GMIM ministry who were rebaptized by being immersed and some did not want to eat pork anymore and some did not have activities on Saturdays but at worship times on the day Sunday. The presence of new schools that offer new teachings also makes the church have to be extra hard to deal with all of them. The Evangelical Christian Church in Minahasa, which in the course of its church history to land the Gospel until it stands alone, cannot be separated from so many problems both from the natives (Minahasa people) themselves and from within the church itself which in the end also has little influence on the thinking thoughts that exist in the internal community of GMIM.